Comprehensive characteristics of productive and biological parameters of tench (Tinca tinca Linnaeus, 1758) growing using different cultivation technologies - H. Kurinenko; R. Konopelskyi (Ribogospodarsʹka Nauka Ukraïni)
Purpose. To conduct a comparative analysis of growth dynamics, exterior and reproductive parameters of tench broodstock grown at different levels of intensification of the technological process.